Pengembangan Usaha Mikro Kecil dan Menengah Telur Asin di Desa Bukit Raya - Hambali, dkk., Hambali (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
Each village has its own flagship UMKMs, UMKMs are businesses that help the Indonesian economy. In developing superior UMKMs from Bukit Raya Village, of course there is a product produced by the surrounding community, Bukit Raya Village takes Salted Eggs as a superior product that is favored by many people and is a typical Indonesian food. The Kukerta team visited the salted egg production site to explain and discuss efforts to improve and advance UMKMs in order to achieve a wider target market in order to be able to compete with other micro, small and medium enterprises. The purpose of this activity is to find out how the process of making salted eggs is the leading UMKM in Bukit Raya Village. The method used in this program is a descriptive method. The results of this activity received a positive response from UMKM owners, and provided production support goods, namely location signs and banner designs for salted eggs. The purpose of this salted egg banner installation is to promote, advertise, and provide information on salted egg products to the wider community, so that many people know and are interested in buying salted eggs that are marketed.